Tribalism The Evolutionary Origins of Fear Politics - Hobfoll, Stevan E. (Springer International Publishing, 2018)
Unearthing the most primal motivations behind the fear politics movements sweeping across the USA, Europe, and the Middle East, Stevan E. Hobfoll examines how the increasing sense of threat from the political and cultural "other" or "outsider" engenders an evolutionary, built-in "defend and aggress" response. This deep-wired evolutionary response is a defining aspect of our tribal origins and has allowed for the rise of propaganda, extremist politics, and-in turn-violence. In this timely work, which binds theories in psychology, sociology, evolution, biology, linguistics, iconography, rhetoric, and religion, Hobfoll explores the tribalist roots of radical militant Islam, violence against women, white supremacy, the rise of authoritarian leaders, and an increasingly polarized and uncompromising political landscape. Grounded in evolutionary psychological research, Hobfoll's long term study of stress, and in conversation with contemporary academic literature, Tribalism not only offers an explanation for society's worst impulses, but also points us towards the best protections against tribalism and other evolutionary traps.